From oil wealth to green growth - An empirical agent-based model of recession, migration and sustainable urban transition. (September 2018) - Ge, Jiaqi; Polhill, J. Gareth; Craig, Tony; Liu, Nan
Abstract: This paper develops an empirical, multi-layered and spatially-explicit agent-based model that explores sustainable pathways for Aberdeen city and surrounding area to transition from an oil-based economy to green growth. The model takes an integrated, complex systems approach to urban systems and incorporates the interconnectedness between people, households, businesses, industries and neighbourhoods. We find that the oil price collapse could potentially lead to enduring regional decline and recession. With green growth, however, the crisis could be used as an opportunity to restructure the regional economy, reshape its neighbourhoods, and redefine its identity in the global economy. We find that the type of the green growth and the location of the new businesses will have profound ramifications for development outcomes, not only by directly creating businesses and employment opportunities in strategic areas, but also by redirecting households and service businesses to these areas. New residential and business centres emerge as a result of this process. Finally, we argue that industries, businesses and the labour market are essential components of a deeply integrated urban system. To understand urban transition, models should consider both household and industrial aspects. Highlights: An empirical, multi-layered and spatially-explicit agent-based model has been developed to study urban transition. An integrated, complex system approach has been used to model interconnected agents. Spatial planning has important indirect ramifications in the long-run development of an urban area. Industries, businesses and the labour market should be included in urban system modelling.